A phase I trial of palbociclib plus bortezomib in previously treated mantle cell lymphoma. Issue 12 (15th October 2019) - Martin, Peter; Ruan, Jia; Furman, Richard; Rutherford, Sarah; Allan, John; Chen, Zhengming; Huang, Xiangao; DiLiberto, Maurizio; Chen-Kiang, Selina; Leonard, John P.
Abstract: In mantle cell lymphoma (MCL), cyclin D1 combines with CDK4/6 to phosphorylate Rb, releasing a break on the G1 to S phase cell cycle. Palbociclib is a specific, potent, oral inhibitor of CDK4/6 capable of inducing a complete, prolonged G1 cell cycle arrest (pG1) in Rb+ MCL cells. The proteasome inhibitor bortezomib is approved by the US Food and Drug Administration for treatment of mantle cell lymphoma. Palbociclib-induced pG1 appears to sensitize MCL cells to killing by low-dose bortezomib, potentially improving its activity and tolerability. We conducted a phase 1 trial of palbociclib plus bortezomib in patients with previously treated MCL (NCT01111188). Patients received palbociclib at 75 mg (dose level 1), 100 mg (dose level 2), or 125 mg (dose levels 3 and 4) on days 1–12 of each 21-day cycle in addition to intravenous bortezomib 1.0 mg/m 2 (dose levels 1, 2, 3) or 1.3 mg/m 2 (dose level 4) on days 8, 11, 15 and 18. A total of 19 patients with a median age of 64 and an average of 2 prior therapies were enrolled. Two subjects experienced dose limiting toxicity (DLT): thrombocytopenia (dose level 1) and neutropenia (dose level 3). Although no DLTs were seen at dose level 4, all patients required dose delays during cycle 2 due to cytopenias, and the study team decided to stop the trial. Four of 19 patients achieved a clinical response, including one patient with a complete response. Three patients received treatment for more than one year, including one patient receiving single-agent palbociclib for more than 6 years. The combination of palbociclib 125 mg on days 1–12 plus bortezomib 1.0 mg/m 2 on days 8, 11, 15, and 18 of a 21-day cycle is feasible and active in previously treated MCL, with the primary toxicity being myelosuppression. The regimen may be worthy of further evaluation in patients with non-blastoid MCL following failure of other newer agents.